Morphological diagnostic criteria of autoimmune gastritis - Ye. A. Losik; L. S. Selivanova; T. V. Antonova; T. L. Lapina; Alexander S Tertychny; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To specify morphological features of autoimmune gastritis (AIH) and to indicate options for morphological diagnosis of this disease. Material and methods. The gastric biopsy specimens of 8 patients received at routine esophagogastroduodenoscopy (EGDS) were investigated. Biopsy specimens were processed by the standard technique. Serial sections were stained by hematoxyline and eosine, and immunehistochemical standing with anti-chromogranin A antibodies serum. Results. Morphological features of autoimmune gastritis, including cases with primary morphological diagnosis in contrast to the cases with primary serological diagnosis by anti-parietal cells antibodies are presented. The options of polyps or pseudopolyps detection at upper endoscopy are described which at morphological investigation correspond to sites of noninvolved mucosa of the body of stomach or hyperplastic foveolar layer. AIH can be characterized by metaplastic and non-metaplastic atrophy (intestinal and pseudo-pyloric metaplasia), pancreatic metaplasia, inflammatory infiltration with glandular epithelium destruction and T-lymphocyte emperipolesis, as well as by lipomatosis in lymphoid accumulations and neuroendocrine cell hyperplasia. Conclusion. Presented diagnostic features at autoimmune gastritis can be combined that is characteristic for this disease entity. In difficult cases at suspicion for AIH immunehistochemical staining for chromogranin A helps to diagnose neuroendocrine ECL cell hyperplasia, to specify its variant and to confirm the diagnosis.